2010
DOI: 10.1108/10444061011016614
|View full text |Cite
|
Sign up to set email alerts
|

Team identification, trust and conflict: a mediation model

Abstract: Purpose -The current study aims to address the relationship between trust, team identification, and team conflict. Specifically, it aims to examine whether trust in peers mediates the relationship between team identification and team conflict. Design/methodology/approach -This is an empirical paper based on two field studies. In Study 1, 241 employees in a US Fortune 500 company distributed in various and mostly R&D teams were surveyed. In Study 2, 205 employees in a health care organization in the Midwest wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 101 publications
(144 reference statements)
5
70
0
Order By: Relevance
“…(Pratt, 1998). Team identity refers to the extent to which a team member sees the team's goals as their own and feels interconnected with the team's fate (Han & Harms, 2010). Previous research has found a positive relationship between team identity and team performance (Han & Harms, 2010;Lembke & Wilson, 1998), and the importance of cultivating a sense of "we" (as opposed to "I") in a team setting.…”
Section: Team Identitymentioning
confidence: 99%
See 4 more Smart Citations
“…(Pratt, 1998). Team identity refers to the extent to which a team member sees the team's goals as their own and feels interconnected with the team's fate (Han & Harms, 2010). Previous research has found a positive relationship between team identity and team performance (Han & Harms, 2010;Lembke & Wilson, 1998), and the importance of cultivating a sense of "we" (as opposed to "I") in a team setting.…”
Section: Team Identitymentioning
confidence: 99%
“…Team identity refers to the extent to which team members see the team's goals as their own and feel interconnected with the team's fate (Han & Harms, 2010). Previous research has found evidence for a positive relationship between team identity and team performance (Han & Harms, 2010;Lembke & Wilson, 1998;Pratt, 1998). Teams who know one another and strongly identify with the team, its goals, and mission are more motivated to exert effort for the overall team success (Tyler & Blader, 2000).…”
Section: Army Maj)mentioning
confidence: 99%
See 3 more Smart Citations